Interstitial lung disease and microscopic polyangiitis in chilean patients - Wurmann, Pamela; Sabugo, Francisca; Elgueta, Fabian; Mac-Namara, Macarena; Vergara, Karen; Vargas, Daniela; Molina, Maria Luisa; Diaz, Juan Carlos; Gatica, Hector; Goecke, Annelise (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Objective: To describe the clinical and serological patients characteristics with Microscopic Polyangiitis (MPA) and Interstitial lung disease (ILD). Methods: Of all the patients with AAV diagnosed between 2007-2017 at the Hospital Clinico Universidad de Chile, those with MPA and ILD were selected and studied retrospectively. Results: All patients were Hispanic; median age at diagnosis 65 years (32-84). 59% were female. All were positive for p-ANCA, 16 patients for MPO. Most common manifestations were constitutional symptoms, weight loss and fever. CT-Scans patterns were Usual Interstitial Pneumonia (UIP) in 10 patients, Nonspecific Interstitial Pneumonia (NSIP) in 6 and fibrosis not UIP or NSIP pattern in 1. In 6 cases, ILD was diagnosed 0.5-14 years before MPA and concomitantly in 11. Conclusions: Although infrequent, Microscopic Polyangiitis should be suspected in patients with ILD particularly if extra-pulmonary manifestations that rise the possibility of a systemic illness are present, regardless of the time elapsed between the latter and the diagnosis of this type of lung involvement.